Pengaruh Strategi Pembelajaran Berbasis Masalah dan Minat Belajar Terhadap Kemampuan Berpikir Kritis dan Hasil Belajar Siswa pada Materi Sistem Pencernaan Makanan Manusia di MAS Amaliyah Sunggal - Ridho Fenni Naputri; Syarifuddin Syarifuddin; Ely Djulia (Magister Pendidikan Biologi, Universitas Negeri Medan, 2016)
This study was aimed to determine effect on: (1) Problem based learning strategy toward critical thinking skills; (2) Learning interest toward critical thinking skills; (3) Interaction between problem based learning strategy and learning interest toward critical thinking skills; (4) Problem based learning strategy toward students’ learning outcomes; (5) Learning interest toward students’ learning outcomes; and (6) Interaction between problem based learning strategy and learning interest toward students’ learning outcomes. Subjects in this study are taken as much as 3 classes is determined by a cluster random sampling. Determined learning class in research is 2 classes with sample of 38 people per class. . Based on the results show that there are significant effect on (1) Learning model toward critical thinking skills which obtained Fcount>Ftable (6,971>2,50) and probability value is 0,010<0,05; (2) Learning interest toward critical thinking skills which obtained Fcount>Ftable (24,949>2,50) and probability value is 0,000<0,05; (3) Interaction between learning model and learning interest toward critical thinking skills which obtained Fcount>Ftable (4,140>2,50) and probability value is 0,046<0,05; (4) Learning model toward students’ learning outcomes which obtainde Fcount>Ftable (25,269>2,50) and probability value is 0,000<0,05; (5) Learning interest toward students’ learning outcomes which obtained Fcount>Ftable (13,888>2,50) and probability value is 0,000<0,05; and (6) Interaction between learning model and learning interest toward students’ learning outcomes which obtained Fcount>Ftable (4,291>2,50) and probability value is 0,042<0,05. Based on this study can conclude that there are significant effect of strategy, interest, and interaction between learning strategy and learning interest toward critical thinking skills and students’ learning outcomes on the topic in digestive system of human at MAS Amaliyah Sunggal. This cases are expected to provide information for teachers and schools to use problem based learning strategy and learning interest to improve critical thinking skills and student’s learning outcomes.